Hooked on a feeling? An interpretive study of organizational identity (dis)continuity during strategic change programmes† - Harikkala-Laihinen Riikka (Elsevier Ltd, 2026)
This paper explores how organizational members perceive identity (dis)continuity when they are caught in the crossfire during strategic change programmes. Illustrative data stems from a Finnish company that underwent a change from family ownership to corporate investor ownership, resulting in a broad organizational transformation. The findings indicate that organizational members perceive identity (dis)continuity during strategic change programmes in many ways, influenced by both the organizational context and personal experience. The organization's ability to signal continuity and the strength of the individual member's emotional bond to the old organization seem to be key elements in directing member perceptions towards identity continuity or discontinuity – in other words, liminality. The organizational identity perspective improves our understanding of the individual-level dynamics of strategic change programmes, helping managers engage and motivate members to execute the change. In effect, strategic change programmes where programme management understands and acknowledges the role of identity may improve organizational outcomes.